Physical, chemical and sensory properties of cassava (Manihot esculenta) – sweet potato (Ipomoea batatas) gari - Karim, O.R.; Adebanke, B.M.; Akintayo, O.A.; Awoyale, W. (National University of Food Technologies, 2016)
Introduction. Food safety is one of the problems facing sub-Sahara African countries like Nigeria. The use of wholesome indigenous crops and improved methods of production of major foods is a way forward. Materials and methods. A factorial research design was used to obtain eight samples of cassava and sweet potato gari from three modifications of the traditional production method for gari. Effects of these methods on the physical, chemical and sensory properties of the gari were evaluated using standard methods. Results and discussion. The results revealed that the inclusion of sweet potato significantly (p<0.05) influenced the proximate composition of the cassava-sweet potato gari and the values are also within the recommended levels for quality gari. Moisture content ranged from 10.10 to 12.30%, crude fibre 1.93 to 1.98%, ash content 1.13 to 1.31%, protein content 1.43 to 4.29%, and carbohydrate content 78.11 – 83.59%. The cyanide contents ranged from 0.58 to 2.16 mg/100 g, with 100% cassava gari having the highest while 100% sweet potato gari recorded the lowest. A decrease in porosity from 40 ± 2 % for the 100% cassava gari to 27.33 ± 2 % for sweet-potato gari was observed. The particle size of the sweet potato gari had the highest angle of repose of 38° while 100% cassava gari recorded the lowest angle of repose (29°). The swelling index of the samples ranged from 330 to 450% and100% sweet potato gari had the highest loose and packed densities. The sensory evaluation results showed that the cassava sweet potato (10%) gari was rated the best for colour (8.07), texture (7.67), and aroma (6.87), while 100% cassava gari had highest value for taste (7.47), and both shared the highest value (7.60) in overall acceptability. Conclusions. The study showed that 10% sweet potato can traditionally be added to cassava for quality gari production.